An effective cloud-based smart home appliances automation in IoT using PHMM model. (31st August 2021) - Sundarakumar, M.R.; Sankar, S.; Reddy, S.R.S.
Internet of things (IoT) is an emerging and innovative approach to control the home appliances remotely. A trillion of devices are connected to the internet that are controlled and monitored in real-world applications. The main goal is to provide the automation for home appliances using IoT. Wireless sensor networks (WSNs)-based home automation systems are very difficult to manage with the devices using a centralised approach due to the mobility. To solve this issue, wireless home automation system (WHAS) is proposed, which uses the predictive hidden Markov model (PHMM) to control the devices efficiently and conserves the energy utilisation among the devices. The status of the devices are monitored continuously and selecting the device operation either in manual mode or automatic mode using the PHMM model. The proposed approach conserves more energy than traditional methods.